Sacrificial 3D printing of shrinkable silicone elastomers for enhanced feature resolution in flexible tissue scaffolds. (November 2020) - Davoodi, Elham; Montazerian, Hossein; Khademhosseini, Ali; Toyserkani, Ehsan
Abstract: Silicone implants and scaffolds are emerging as potential replacement of flexible tissues, cosmetic and biomedical device implants due to their bioinert and flexible characteristics. The state-of-the-art direct-write silicone three-dimensional (3D) printers however cannot easily 3D print structures with sub-millimeter dimensions because of high viscosity and long curing times of their prepolymers. In the present study, a template-assisted 3D printing of ordered porous silicone constructs is demonstrated. The sacrificial molds were fabricated by low-cost and well-accessible material extrusion 3D printers. The 3D printed molds represent interconnected tortuous high specific surface area porous architectures based on triply periodic minimal surfaces (TPMS) in which the silicone prepolymer is cast and cured. We engineered silicone prepolymer with additives allowing on-demand structural shrinkage upon solvent treatment. This enabled 3D printing at a larger scale compatible with extrusion 3D printer resolution followed by isotropic shrinkage. This procedure led to a volumetric shrinkage of up to ~70% in a highly controllable manner. In this way, pore sizes in the order of 500–600 µm were obtained. The porous constructs were characterized with full strain recovery under extreme compressive deformations of up to 85% of the initial scaffold length. We further demonstrated the ability to infill cell-laden hydrogels such as gelatin methacryloyl (GelMA) into the interconnected pores while maintaining the cell viability of ~90%. Graphical abstract: Image, graphical abstract